RELIGIOUS JOURNEYS AND TOURISM SECTOR BUSINESS ADMINISTRATION: SUSTAINABLE LOGISTICS FOR ZIYARAH TO MADINAH (S. ARABIA), AMPEL (INDONESIA) AND SYLHET (BANGLADESH) - A. A. Rahman (Journal of Management and Business, 2009)
This research uses a subjective observation of objective facts through the sociological research participation-observation method, in three pilgrimage sites-Madinah (S. Arabia), Ampel/Surabaya (Indonesia), and Sylhet (Bangladesh) suggest some hypotheses and corresponding policy recommendations, for further and empirical research for testing, corroboration, modification and or elaboration. These include, 1)A batch of religiously trained and sensitive volunteers or officials also trained in peace-keeping, as in place in Madinah Prophet's Mosque, might be a better instrument of maintaining law and order than normal police force or total or near total absence of any peacekeeping mechanism at all, as is the case with Surabaya’s Ampel and Sylhet Dorgan; 2)A system of relatively inexpensive but clean and hygienically well-maintained and modernized inns within or attached to local family homes-than expensive hotel chains-in the immediate and near vicinity of the pilgrimage sites might be a better and more sustainable option for pilgrims’ accommodation; 3)Health and hygiene concerns need utmost priority in such overcrowded sites with visitors from diverse sources, and preventive as well as curative measures with adequate toilets and bathing facilities, and adequate free clinics available on the sites, as place in the case of Madinah also need to be introduced in Ampel and Sylhet; 4)As a part of the health and hygiene concern, adequate preventive measures need to be introduced in all such sites, to fight short and long-term problems posed by odor and noise pollution. Further, empirical research suggested to test and corroborate, nullify or modify these hypotheses may start with simple survey-research quantitative analyses of data collected from these three sites. Further sites from other places may be added.